Management of Isolated Atherosclerotic Stenosis of the Common Femoral Artery: A Review of the Literature. (May 2017) - Halpin, David; Erben, Young; Jayasuriya, Sasanka; Cua, Bennett; Jhamnani, Sunny; Mena-Hurtado, Carlos
Objective: Common femoral endarterectomy (CFE) remains the standard of care for treatment of atherosclerotic stenosis of the common femoral artery (CFA). Endovascular interventions have become the first-line therapy for atherosclerotic disease of the aortoiliac and femoropopliteal systems. Recent reports have documented high rates of technical success and low rates of complications with endovascular management of CFA stenosis. This study is a contemporary review of the surgical and endovascular literature on the management CFA stenosis and compares the results of these methods. Methods: A search of OVID Medline identified all published reports of revascularization of isolated atherosclerotic CFA stenosis. For each study selected for review, the number of patients, number of limbs treated, percentage of patients with critical limb ischemia, and mean length of follow-up was recorded. Study end points included survival, primary patency, freedom from target lesion revascularization (TLR), freedom from amputation, and complications. Results: The review included 7 CFE studies and 4 endovascular studies. Survival was similar between the groups. Primary patency was consistently higher with CFE compared to endovascular therapy. Freedom from TLR was lower with CFE compared to endovascular therapy. Morbidity and mortality was also higher with CFE compared to endovascular therapy. Freedom from amputation was not consistently reported in the endovascular studies. Conclusion: There is limited data to support endovascular treatment of isolated CFA atherosclerosis. CFE has durable results, but there is significant morbidity and mortality resulting from this procedure. Endovascular interventions have low rates of complications, high rates of technical success, good short-term patency but increased need for repeat interventions when compared to surgery. Further trial data comparing CFE with endovascular therapy is needed to guide the management of CFA stenosis.